Warunkowe zwolnienie z reszty kary pozbawienia wolności z perspektywy problemów z ustalaniem treści i kierunku prognozy kryminologicznej - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The aim of the study is to elaborate on conditional release parole in view of the evolution and development of contemporary criminal executive law. One of the objectives of the study is to contemplate on the meaning of the notion of criminological forecasting as well as the rules and the way to set its direction. The study also investigates the problem of realization of political-criminal assumptions which can be formulated for the institution of parole and the influence of these assumptions on the regulations determining the content of parole.
Keywords: zwolnienie warunkowe; probacja (prawo); prognozy kryminologiczne; kara pozbawienia wolności